ANTI-AGING PEEL-OFF MASK OF DRAGON FRUIT PEEL EXTRACT (HYLOCEREUS POLYRHIZUS) - Wahdaningsih, Sri; Rizkifani, Shoma; Utari, Eka Kartika (Jurnal Farmasi Sains dan Praktis, 2023)
Antioxidants can be used to protect the skin from damage caused by oxidation to prevent premature aging. The more increasing consumption level of red dragon fruit (Hylocereus polyrhizus) affects the amount of unused remaining fruit peels. In fact, the peel of red dragon fruit is considerably potential for natural antioxidant. Pitaya or dragon fruit is reported to contain betacyanin color pigment, with antioxidant activity. The use of cosmetics containing antioxidant compounds can prevent premature aging due to free radicals. One of the interesting forms of cosmetic preparations for skin care is the peel-off gel mask. The base that can be used as a film former for peel-off gel facial masks is polyvinyl alcohol (PVA). This study aims to determine the effectiveness of red dragon fruit peel extract peel-off masks as anti-aging. Anti-aging effectiveness testing was carried out on 10 volunteers and divided into two groups, namely the blank group (F0) and the extract group (FIII) for four weeks, and anti-aging activity was measured using a skin analyzer). Based on the results and discussions in this study, it can be concluded that the application of a peel-off mask of red dragon fruit peel extract (Hylocereus polyrhizus) is effective for repairing the skin and providing an anti-aging effect.